CUT-OFF PARAMETRES FOR RESERVES CALCULATION OF CONSTRUCTION STONE DEPOSITS WITHIN THE DISTRIBUTION OF GLACIAL SEDIMENTS - LUKOMSKYI, Vladyslav; KURYLO, Mariia (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The study objects are crystalline rocks deposits, which are developed for the production of construction and crushed stone, and are localized within the distribution of glacial and fluvioglacial deposits. Traditionally, the cut-off parameters for such deposits mainly take into account the requirements for the quality of the main mineral, the mining depth and the overburden thickness. The study systematizes the cut-off parameters for reserves calculating for deposits of construction and crushed stone. The cases of assessment of the main mineral, co-occurring and by-product minerals have been determined. Traditionally, the cut-off parameters for such deposits mainly take into account the requirements for the quality of the main mineral, mining depth and the overburden thickness. It was defined that the following parameters are used for the reserves calculation for most objects: 1) stratigraphic definitions of the mineral – mineral – Lower Proterozoic unaltered granites and weathered granites of the Uman complex or other crystalline rocks; 2) mineral quality parameters, where the main physical and mechanical properties determine the suitability of raw materials for the production of crush stone and for the production of rubble stone; 3) the maximum thickness of overburden is from 1 to 28.5 m; 4) defining security cells, explosive zones, etc.; 5) the maximum mining depth and horizon of reserve calculation. The maximum total specific activity of natural radionuclides in mineral samples should not exceed the value of 370 Bq/kg. The products of crushing granite into fractional crushed stone, which are represented by screening, are also evaluated and must meet the requirements of the standard "Sand from screenings of crushing igneous rocks for construction works. Specifications". This study examines the effectiveness of comprehensive development of construction and crushed stone deposits. In particular, it is proposed to consider overburden rocks, which are represented by deposits of glacial origin, as accompanying minerals, which have the directions of using raw materials in the construction industry and landscape design. The limit coefficient of overburden for the studied deposits is calculated. The dependence of the limit coefficient of overburden on the change in the cost of mineral extraction and overburden work is determined.